(untitled) (Journal of Partial Differential Equations, 2020)
"This paper deals with the quenching solution of the initial boundary value problem for a class of semilinear reaction-diffusion equation controlled by two absorption sources in control system and estimate upper bound and lower bound of the quenching time. We point that the number of absorption sources influences the time of quenching phenomenon. The solution can solve some boundary value problem in control system."